Effect of Dissolved Oxygen on the Growth, Sporulation and Larvicidal Activity of Bacillus sphaericus 2362 - Abdul Karim, Mohamed Ismail (Universiti Putra Malaysia Press, 1996)
Bacillus sphaericus produces bacterial protein toxin capable of killing larvae of mosquitoes which spread diseases such as filariasis, encephalitis and malaria. In batch culture, a maximum spore count of 2.9 x 109/ml media was obtained after 48 h cultivation. In continuous culture, a dilution rate of 0.10 hr- I was found to give a higher spore count than 0.15 h- 1 and 0.2 h- I dilution rates. Kinetic studies on dissolved oxygen (DO) levels showed that 20,50 and 100% gave rapid formation of free spores, whilst 5% DO gave poor results. Cells grown at 5, 20 and 50% DO levels gave comparable values of mosquito-larvicidal activity while those grown at 100% DO were significantly less toxic.